Biohydrogen production from brown algae fermentation: Relationship between substrate reduction degree and hydrogen production. (November 2022) - Li, Weiming; Lu, Lihui; Cheng, Chi; Ren, Nanqi; Yang, Shang-Tian; Liu, Meng
Graphical abstract: Highlights: H2 production of seaweed hydrolysate was studied with C. tyrobutyricum . Acetate assimilation significantly promotes mannitol digestion and H2 evolution. Mannitol generates more reducing power for hydrogen evolution pathway. Mannitol evolves 42.02% higher H2 and 40.82% higher butyrate than glucose. High H2 yield (2.33 mol/mol) and energy recovery (41.20 %) were obtained from seaweed. Abstract: In this study, mannitol and mannitol-rich seaweed were fermented to investigate the relationship between substrate reduction degree and hydrogen production performance. The results showed that acetate was required in mannitol fermentation with an optimum acetate/mannitol mass ratio of 1:5. Hydrogen production and yield of mannitol fermentation reached 123.76 mL and 2.12 mol/mol-mannitol, respectively, 42.02 % and 26.95 % higher than that of glucose, respectively. The acetate was fully assimilated and the butyrate selectivity reached 100 % in the effluent. Redox potential and electron distribution showed that mannitol increased the overall electron input from mannitol and acetate, leading to the increase in hydrogen and butyrate generation. Hydrogen yield reached 2.33 mol/mol-mannitol with brown algae hydrolysate, which was the highest ever reported. This study demonstrated that substrate with a higher reduction degree could yield higher hydrogen and showed the great application potential of brown algae fermentation for the co-production of hydrogen and butyrate.